Analysis of Information Quality on the COVID-19 Website Riau Government, Indonesia - Rizki Erdayani; Muslim Afandi; Syed Agung Afandi; Hijratul Aswad (JPASDEV : Journal of Public Administration and Sociology of Development, 2023)
Riau is the area with the highest number of COVID-19 cases, ranking seventh nationally and the highest in Sumatra. This study aims to analyse the quality of information on the Riau Government's COVID-19 website. This study uses a qualitative approach, with data obtained through observation and documentation. The results of this study indicate that the accuracy of the information displayed on the Riau Government's COVID-19 website is doubtful because there are differences in the data displayed. Furthermore, the information on the Riau Government's COVID-19 website is also not updated regularly, so the data is invalid. Although there are no guidelines for the development of the local government's COVID-19 website, the information displayed on the Riau Government's COVID-19 Website is considered relevant according to its purpose, and in general, the type of information displayed is aligned with the National COVID-19 Handling Task Force Website, but not all the content of the information contained on the Riau Government's COVID-19 website is relevant in terms of data appearance according to the features available on the website. In addition, because the data is not updated regularly, the information available on this website is incomplete. This study recommends that the Riau Government manage the COVID-19 website optimally. This can be done by coordinating with all stakeholders so that they have valid information. In addition, the Riau Government must also regularly update data and adjust website features with public data.